Judgment and pleasure – or on “the key to the critique of taste”. Notes on § 9 of the third ’Critique’ - Barbosa, Ricardo (Discurso, 2023)
In his “Analytic of the Beautiful”, Kant often anticipates the problem of the “Deduction of the Pure Aesthetic Judgments”, mixing the investigation of the conditions under which a judgment of taste can be considered a pure judgment with the justification of its claim to universality, as in §9, in which he discusses whether pleasure precedes or succeeds the judging of the object. This question is pointed out as “the key to the critique of taste” because its answer already puts in evidence what is affirmed a priori in a judgment of taste.